2015
DOI: 10.1074/jbc.m115.679266
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Insulin Resistance Following Chronic Activation of the CREB Coactivator CRTC2

Abstract: Background: Loss of CRTC2 improves insulin sensitivity, but it is unknown if chronic CRTC2 activity causes hepatic insulin resistance. Results: Liver expression of constitutively active CRTC2 increased hepatic glucose production, despite compensatory increases in FOXO1 phosphorylation. Conclusion: Persistent increases in CRTC2 activation promote hepatic insulin resistance. Significance: Disrupting CREB signaling in liver could provide therapeutic benefit against insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 34 publications
(29 reference statements)
4
20
0
Order By: Relevance
“…Taken together, it seems that the role of CRTC2 in hepatic insulin sensitivity is dependent on certain circumstances (eg, diet and fatty liver). Acute or chronic, overactivated or deactivated CRTC2 may have various effects on hepatic insulin signaling . We agreed with the conclusion from Han et al that tight regulation of hepatic CRTC2 function is critical in the maintenance of energy and metabolic homeostasis in mammals.…”
Section: Discussionsupporting
confidence: 91%
“…Taken together, it seems that the role of CRTC2 in hepatic insulin sensitivity is dependent on certain circumstances (eg, diet and fatty liver). Acute or chronic, overactivated or deactivated CRTC2 may have various effects on hepatic insulin signaling . We agreed with the conclusion from Han et al that tight regulation of hepatic CRTC2 function is critical in the maintenance of energy and metabolic homeostasis in mammals.…”
Section: Discussionsupporting
confidence: 91%
“…Previous reports have shown that CRTC2 has different effects on lipid metabolism under different conditions . For example, on a chow diet, the chronic overexpression of CRTC2 activated CRTC2‐induced hepatic steatosis and higher levels of hepatic TG, as expected in hyperglycemia .…”
Section: Discussionmentioning
confidence: 88%
“…Consistent with this crosstalk, the CREB–CBP–CRTC2 module exerts stronger control over the expression of G6pc during the first 6 h of fasting in mice, whereas the FOXO1–PGC1α module has a larger role in stimulating G6pc transcription over longer durations (~18 h) of fasting in mice 116 . As predicted, Crtc2 –knockout mice had fasting hypoglycaemia and mice with adeno-associated virus (AAV)-mediated overexpression of constitutively active CRTC2 were hyperglycaemic 117,118 .…”
Section: Control Of Hepatic Gluconeogenesismentioning
confidence: 59%